(untitled) (Revista de Psicología, 2021)
There still lacks preciseness about the nature of the connection between psycholinguistic variables and the core of conceptual meaning. This article explores the relation between Age of Acquisition (AoA), Imaginability, Semantic richness, Familiarity and Concreteness in the constitution of semantic core meaning. We used a key recognition task, designed with 120 concepts and their first 5 attributes, extracted from the Semantic Attributes Norms in Spanish. 300 students took part in a concept recognition task, where they were asked to recognize certain concepts through different triads of attributes. The most influential variables were AoA and Imaginability. These results are congruent with studies that suggest the AoA as the most appropriate variable to explain results in lexical decisions tasks.